Implementasi Metode Stifin Dalam Optimalisasi Pengembangan Bakat Murni Santri Di Pesantren Muhajirin Bandung - Samsudin, Arif; Hanafiah, Hanafiah; Fatkhullah, Faiz Karim; Sohim, Badru (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to implement the STIFin method in optimizing the development of pure talents of students at the Muhajirin Bandung Islamic Boarding School. The method used by the author is a qualitative method with a qualitative experimental approach (experimental qualitative research). Where experimental research is a research that utilizes modern technology sources in the form of fingerprint test tools to obtain research data. The results showed that the implementation of the STIFIn method at the Muhajirin Bandung Islamic Boarding School has been proven to help optimize the development of pure talents of students. With a more personal approach and based on brain characteristics, students can be more focused and effective in developing their potential. This success can be seen from the increasing achievements of students both in academic and non-academic fields. Keywords: implementation, method, students